The effect of chitosan addition on the tensile strength characteristics of carrageenan from Eucheuma spinosum - Margareta, Tanti; Ningsih, Ellis Nurjuliasti; Hendri, Muhammad; Amal, Ikhlasul (UIN Sunan Ampel Surabaya, 2026)
The accumulation of non-biodegradable plastic waste and its detrimental effects on the environment underscore the imperative to develop sustainable packaging alternatives, such as edible films. In this study, the incorporation of chitosan was investigated to enhance the mechanical properties of an edible film based on carrageenan extracted from the seaweed Eucheuma spinosum. The carrageenan was extracted from E. spinosum cultivated in the coastal waters of Ketapang, Lampung, Indonesia and its yield and dry shrinkage were determined. Edible films were then fabricated by varying the concentrations of carrageenan and chitosan, with glycerol employed as a plasticiser. Characterisation included tensile strength testing, thickness measurement using a micrometer, and morphological analysis via scanning electron microscopy (SEM). The results indicated that tensile strength increased with the addition of chitosan up to an optimal concentration; beyond this point, further addition resulted in a decline in tensile strength. The maximum tensile strength achieved was 15.31 MPa, and film thickness ranged from 0.06 to 0.20 mm, thereby meeting the requirements of the JIS Z 1707:2019 standard. Morphological analysis revealed a smooth surface but a non-homogeneous particle distribution, suggesting that the mixing process was not yet fully optimised. Overall, the combination of carrageenan and chitosan significantly improved the physical and mechanical properties of the edible film, indicating its potential as a safe, biodegradable, and environmentally friendly food-packaging material.